2015
DOI: 10.1111/srt.12241
|View full text |Cite
|
Sign up to set email alerts
|

Facial skin physiology recovery kinetics during 180 min post‐washing with a cleanser

Abstract: This study indicated that each of the skin parameters was restored at defined time points post-cleansing. Our result could be a useful reference to set the resting time in the estimation of skin bioengineering parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 8 publications
1
20
2
Order By: Relevance
“…Exfoliation of the uttermost layers of the stratum corneum also removes restrictions of the excretory ducts of the sebum glands and reduces the inflammation. However, intensive degreasing can damage the skin barrier and cause dryness and redness . This in turn may promote the colonization with pathogenic bacteria.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Exfoliation of the uttermost layers of the stratum corneum also removes restrictions of the excretory ducts of the sebum glands and reduces the inflammation. However, intensive degreasing can damage the skin barrier and cause dryness and redness . This in turn may promote the colonization with pathogenic bacteria.…”
Section: Discussionsupporting
confidence: 58%
“…There are various types of skin care for oily and acne‐prone skin . Many of these products are based on surfactants which can irritate the skin …”
Section: Introductionmentioning
confidence: 99%
“…We suppose that sebum levels decreased after washing and returned insufficiently towards the baseline point; therefore, there were no drastic changes observed between these circumstances. According to Eo et al ., sebum secretion significantly decreased at 20 min after cleansing and significantly increased over time (until 180 min); sebum secretion had the biggest change among all other skin properties (skin hydration, sebum, TEWL and pH).…”
Section: Discussionmentioning
confidence: 99%
“…Hydration level, sebum secretion and skin greasiness increased, while TEWL and pH decreased after 90-min exposure to indoor conditions. Eo et al 21 reported that cleansing the skin results in decreased hydration and sebum secretion and increased TEWL and then these values are restored after 40-120 min. M€ ucke et al 22 stated that washing the skin increases the pH of the skin, which did not return to baseline completely after 90 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation